Pengaruh Penambahan Daun Stevia (Stevia rabaudiana) Terhadap Aktivitas Antioksidan Minuman Herbal Teh Daun Kelor (Moringa oleifera L.) - Sari, Dian Yufita; Tuju, Thelma D. J.; Assa , Jan R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
The purpose of this research is to analyze antioxidant activity and to obtain the best formulation of herbal drink of moringa leaf tea with the addition of stevia leaves. The method used in this study was a descriptive method with formulation A (90% moringa leaves and 10% stevia leaves), formulation B (80% moringa leaves and 20% stevia leaves), formulation C (70% moringa leaves and 30% stevia leaves), and formulation D (60% moringa leaves and 40%). Based on the results of the antioxidant test, treatment C has a smaller IC50 value of 38,21 ppm, meaning that treatment C has stronger antioxidant activity and based on the total phenol test, treatment C has a higher total phenol content with an average value of 378.09 mg GAE/gr. Based on the results of the panelist preference level test, treatment C (70% moringa leaves and 30% stevia leaves) is the best formulation in terms of taste, aroma and color.